Risk Assessment Using the PFDA-FMEA Integrated Method - Miroslav Čička; Renáta Turisová; Darina Čičková (Kvalita Inovácia Prosperita, 2022)
Purpose: The paper aims to introduce risk assessment in new product development as an important activity for a successful new product launch. A practical example is presented to demonstrate the integration of tools Failure Mode and Effect Analysis (FMEA) and Pythagorean Fuzzy Dimensional Analysis (PFDA) at new product development process, which is a machined component.